THE CRUCIAL INFLUENCE OF TAX MANAGEMENT IN STRATEGIC BUSINESS DECISIONS - Thompson, Michael; Carter, John; Clark, Emily (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In today's dynamic global business environment, enterprises face unprecedented challenges in tax management and risk control. Tax management has evolved beyond a financial concern and is now a critical factor in strategic decision-making. Shifting tax policies, stringent international regulations, and emerging challenges from the digital economy require enterprises to focus on comprehensive tax management and risk analysis. This article explores the evolving landscape of tax management, emphasizing its significance in strategic decision-making.